Peningkatan Kemampuan Pemecahan Masalah Prediksi Soal-Soal Ujian Nasional Mata Pelajaran Matematika Melalui Pendekatan Jigsaw Pada Peserta Didik Kelas IX A SMP Negeri 4 Boyolali Semester Genap Tahun Pelajaran 2012/2013 - Wahyuni, Sri (Universitas Muhammadiyah Surakarta, 2014)
The purpose of this study was to describe the optimization problem solving skills predictions about national exam mathematics courses through Jigsaw approach at a ninth grade students of State Junior High School 4 Boyolali. Subject and source of research data were do students of class IX A. The methods of collecting data were questionnaires, documentation, and test. Data were analyzed using a critical and comparative analysis. Indicators of success or graduation used criteria 5.5 (scale 4) or 55 (scale 100) and a target of 100% completion. The procedure used a classroom action research study conducted in three cycles, the first cycle was as initial condition, while the second and third cycles were as action. The results of research suggest that: (1) the motivation of participants students in learning mathematics courses before cycle can be described increase in the result, namely from before cycle to the first cycle, an increase of before cycle is average of 56 to the first cycle of an average of 58 (4%), of the first cycle an average of 58 the second cycle to an average of 79 of 21 (36%). Thus, the higher motivation of learners shows an impact on learning outcomes. While the mathematics learning outcomes can be described increase in the result, namely from before cycle to the first cycle, an increase of before cycle average of 45 to the first cycle an average of 59 of 14 (31%), from the first cycle an average of 59 to the second cycle mean average 69 of 10 (17%). Finally it can be said that using jigsaw for optimization problem solving skills predictions about national exam mathematics courses is recommended.